Do sujeito ao ciborgue : ciberfeminismo e teoria feminista para o século XXI : narrativas de ativismo feminista em rede no twitter - Coelho, Ana Paula Pereira (2018)
This work is an analysis of the initiatives of feminist groups in Twitter and of cyberfeminists of mobilization and appropriation of science and technology in movement of conquest by equity and freedom. We bring narratives about the groups of cyberfeminists in the network, using the site of relationships Twitter - much used by Brazilian feminists. Donna Haraway, one of the latest authors to work on the quest for a less technophobic femininity, basely or cyberfeministically influencing the term as a basis for political action. The main issue of this work is to destroy as links between feminism and cyborg, the terms and modes of operation of cyberfeminism, narratives and events, in order to analyze the groups' interactions and their diversity